El escritor comprometido versus el escritor profesional - Rivas Sucari, Henry César (2016)
The novel El zorro de arriba y el zorro de abajo Jose Maria Arguedas was written in a singular context. The Cuban Revolution and the emergence of the Latin American Boom determined a way of understanding the social meaning of the work of the writer and the role of the intellectual. One of the most important debates on these issues was the writers Julio Cortázar and José María Arguedas. In this article, we will discuss the arguments of the debate around the concepts of “committed writer” and “professional writer”.